Prevalence and Multidrug Resistance Profiles of Escherichia coli in Dairy Farms - Netsanet Tadesse T (International Journal of Veterinary Science and Research - Peertechz Publications, 2020)
Calf diarrhoea, commonly occur in cattle herds, impacting on the economic viability of cattle operations. A total of 72 calves under 6-months of age, 38 exotic breeds (50% Holstein-Friesian X 25% Jersey X 25% Ogaden) from a dairy farm and 34 local breeds from the Veterinary Clinic, were studied. The secondary data on calf management and impact of calf diarrhoea were collected from the dairy farm, veterinary clinic and subsistence smallholder's dairy farms. Faeces samples were collected from all calves in a sterile container, kept in an ice-cold condition and cultured in the time period of 24 hours. Nearly 49% of the faecal samples were positive for Escherichia coli. E. coli O157 Latex Plate Agglutination test revealed 4.2% and 8.3% prevalence in exotic and local breeds, respectively. Herd size, age group, weaning age were found to be significantly associated (p< 0.05) with the occurrence of E. coli. Antimicrobial susceptibility was tested using agar disk diffusion method, and it was found that E. coli possessed resistance to ampicillin, erythromycin, vancomycin and penicillin. In contrast, amoxicillin, sulphamethoxazole, streptomycin, kanamycin, ciprofloxacin and tetracycline were effective against E. coli.